Regional Integration and Baltic Trade and Investment Performance - Sharer, Robert (IMF Working Papers; Working Paper, 1997)
This paper analyzes the role of regional arrangements in trade and foreign direct investment (FDI) performance in the Baltics. While progress with transition is a key determinant of trade and FDI performance, regional arrangements with Western Europe have helped develop trade and transfer of technology, but have not yet led to export-related foreign direct investment toward the European Union. The main reasons for this are policy uncertainties, need for more progress with transition, and restrictions in the trade agreements, especially on the European Union side. Intra-Baltic integration has not yet led to substantial trade and FDI growth between the Baltics.